Lipid storage myopathy: successful treatment with propranolol. - Martyn, C (1981)
Lipid storage myopathies are a rare but serious cause of muscle weakness characterised by the accumulation of abnormal amounts of neutral fat in type 1 fibres. A case is reported in which the patient presented with weakness of the proximal limb muscles and greatly increased activities of creatine kinase and lactate dehydrogenase. After two years lipid myopathy was diagnosed when electron microscopy confirmed the presence of large numbers of lipid particles within muscle fibres. Twelve years after the initial presentation propranolol (40 mg thrice daily) was started. Strength gradually improved and enzyme activities returned to normal. The improvement in the patient's condition was almost certainly due to the propranolol, although the mode of action of the drug remains unknown.